TELAAH PENAFSIRAN AYAT-AYAT DAN HADIST TENTANG KHITBAH ATAU MEMINANG SERTA ANALISIS KRITISNYA - Liberny, Liberny (El-Sirry: Jurnal Hukum Islam dan Sosial, 2023)
The lesson from verse al-Baqrah verse 235 in the tafsir al-Misbah is that it is haram to khitbah (proposing marriage) to a woman who is still in her iddah period (her iddah period has not yet been completed), openly with lafadz (clear speech). Then, it is permissible to offer yourself to the woman with insinuations (gestures) or words that are not overt (such as saying: 'I want to get married,' or 'If your iddah period is over, discuss with me if you want to get married', or "I am thrilled with a woman like you," or similar words). It is haram to carry out the marriage contract for a woman who is undergoing the iddah period.